2019
DOI: 10.3389/fphar.2019.00886
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dobesilate Restores Autophagy by Inhibiting the VEGF/PI3K/AKT/mTOR Signaling Pathway

Abstract: Objective: Calcium dobesilate (CaD), an effective drug for the treatment of diabetic microvascular complications, especially diabetic retinopathy, is widely used in the clinic. Interestingly, several studies have indicated that CaD is therapeutic for diabetic kidney disease (DKD). Recently, evidence has indicated that altered vascular endothelial growth factor (VEGF) expression and decreased autophagy are the main pathological mechanisms of proteinuria. Thus, this study was conducted to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
0
31
0
1
Order By: Relevance
“…CaD (calcium 2,5-dihydroxybenzenesulfonate) is a vascular protective drug which has been proved to have bene cial effects in vascular diseases such as chronic venous insu ciency and haemorrhoids [27] and is extensively used to treat diabetic retinopathy [28][29][30], choronic venous insu ciency [31] and multiple microangiopathic diseases [32]. In previous studies, the potential mechanisms of CaD improving microcirculation and reducing micro-vascular injury had been investigated as follows [21]: (1) reducing platelet aggregation caused by thrombin or collagen [33]; (2) signi cantly protecting peritoneal vascular from reactive oxygen species (ROS) effects of penetration [34]; (3) inhibiting capillary permeability [35]; (4) alleviating the chronic in ammatory state and improving endothelial cell function [36,37]; (5) reducing endothelial shedding by the synthesis and release of nitric oxide (NO) [38]; (6) reducing platelet aggregation by inhibiting prostaglandin and reduce erythrocyte aggregation and viscosity of suspension [24]; (7) down-regulating the expression of VEGF and broblast growth factor (FGF) to inhibit vascular endothelial cell proliferation [39]; (8) restoring autophagy by inhibiting the VEGF/PI3K/AKT/mTOR signaling pathway [40]. Therefore, based on these mechanisms mentioned above, CaD should be effective in the treatment of macular edema.…”
Section: Resultsmentioning
confidence: 99%
“…CaD (calcium 2,5-dihydroxybenzenesulfonate) is a vascular protective drug which has been proved to have bene cial effects in vascular diseases such as chronic venous insu ciency and haemorrhoids [27] and is extensively used to treat diabetic retinopathy [28][29][30], choronic venous insu ciency [31] and multiple microangiopathic diseases [32]. In previous studies, the potential mechanisms of CaD improving microcirculation and reducing micro-vascular injury had been investigated as follows [21]: (1) reducing platelet aggregation caused by thrombin or collagen [33]; (2) signi cantly protecting peritoneal vascular from reactive oxygen species (ROS) effects of penetration [34]; (3) inhibiting capillary permeability [35]; (4) alleviating the chronic in ammatory state and improving endothelial cell function [36,37]; (5) reducing endothelial shedding by the synthesis and release of nitric oxide (NO) [38]; (6) reducing platelet aggregation by inhibiting prostaglandin and reduce erythrocyte aggregation and viscosity of suspension [24]; (7) down-regulating the expression of VEGF and broblast growth factor (FGF) to inhibit vascular endothelial cell proliferation [39]; (8) restoring autophagy by inhibiting the VEGF/PI3K/AKT/mTOR signaling pathway [40]. Therefore, based on these mechanisms mentioned above, CaD should be effective in the treatment of macular edema.…”
Section: Resultsmentioning
confidence: 99%
“…OD also increased renal lipogenesis marker SREBP1 [ 40 ] and renal inflammatory macrophage proinflammatory markers iNOS and CD68 in kidney tissues [ 3 ]. Furthermore, defective autophagy was confirmed by decreased LC3 and increased P62 expressions [ 10 ]. Moreover, it was associated with an elevation in renal fibrosis markers: TGF-β, PDGFA [ 5 ] and ASMA [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altered autophagy in vascular endothelium, epithelium, pericytes, podocytes and mesangium results in imbalance in cell homeostasis. ORC was reported to be associated with suppressed renal autophagy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study indicates PI3K/Akt/mTOR signaling pathway is hyperactivated in human cancers (Ersahin et al, 2015;Tewari et al, 2019). New studies have found that PI3K/Akt/mTOR proteins are widely expressed in the retinal tissue of diabetic rats (Wang et al, 2019;He et al, 2020). Therefore, inhibition of PI3K/Akt/mTOR is a target for the treatment of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 98%
“…Calcium dobesilate (calcium 2,5-dihydroxybenzenesulfonic acid; CD) was registered by the European Pharmacopoeia and British Pharmacopoeia in 1997 and 1998, respectively (Zhang et al, 2015). It is considered an angioprotective agent with antiinflammatory, antioxidative, and anti-angiogenic properties (Wang et al, 2019) and prescribed as an alternative therapy for the treatment of diabetic retinopathy and other vascular disorders (Berthet et al, 1999;Rabe et al, 2011). CD is indicated and approved for the treatment of DR in several countries, and it is beneficial in the early stages of DR (Simó et al, 2015).…”
Section: Introductionmentioning
confidence: 99%